Insecurity in Implicature as Found in Taylor Swift’s Midnights - Hanif, Imaduddin; Adila, Wildi (Universitas Sebelas Maret, 2024)
People must have insecurities. In expressing the insecurities, they have their own ways, either in explicit or implicit ways. When people implicitly express their insecurities, they flout Grice’s four maxims, which generate implicature. Implicature is not only happening in spoken form but written form as well, like in song lyrics. Taylor Swift is a singer/songwriter who pours her personal experiences into lyrics, and Midnights (3am Edition) is her album filled with such experiences. This study aims to discuss the insecurity signs in the Midnights (3am Edition) song lyrics and then identify the types of implicature in those insecurity signs. This study employed psychological insecurity theory from Maslow (1942) and implicature theory from Grice (1989). This study used descriptive qualitative as the method to analyze the data. Among the 73 data found, the insecurity sign number 4 (Feeling emotionally unstable; feeling tension, conflict, etc.) dominated the findings with 28 data. This result ties in with the album’s concept: about ruminations. Generalized implicature dominated findings with 42 data. Generalized implicature is dominantly used for the purpose of the songs’ reception in the market so broader audiences can understand the songs without having to understand the context or background knowledge about Taylor Swift.